EAST COAST ENDOCRINE TERTIARY CENTRE EXPERIENCE WITH GLUCAGONLIKE PEPTIDE-1 (GLP-1) RECEPTOR AGONISTS - Z, Aina Mardiah; WY, Wan Nur Hidayah; Hua, Goh Hui; RAS, Raja Nurul Azafirah; WA, Siti Sanaa; MA, Masliza Hanuni (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND GLP1-RA is licensed for the treatment of Type 2 Diabetes Mellitus (DM) and weight reduction in obese patients. These agents have been proven effective without increased risk of hypoglycaemia and with significant weight reduction benefits. METHODOLOGY This retrospective cohort study aims to determine the clinical outcome of Type 2 DM and obese patients started on GLP-1RA in Hospital Sultanah Nur Zahirah Terengganu, a tertiary centre in East Coast Malaysia. Clinical outcomes assessed were weight, BMI, total daily dose of insulin (TDD), HbA1c reduction and adverse events after six months of treatment initiation. RESULTS A total of 12 patients were eligible for this study, with a median age of 48 years (24.3). The majority were Malays (91.7%), with 1 Indian. There were equal numbers of males and females. Ten patients had diabetes, with four diagnosed for more than ten years. Nine (75%) were on insulin treatment prior to GLP1-RA initiation, with a median baseline TDD of 66 IU/day (74.0). Two patients were started on GLP1RA for obesity. Eight patients were on injectables, and the remaining were on oral GLP1RA. At baseline, the median weight, BMI and HbA1c were 123.3 kg (49), 48 kg/m2 (18.9), and 8.5% (3.8), respectively. After six months, there were significant reductions in median weight and BMI, 111 kg (47.3) and 41.3 kg/m2 (16.2) (P-value = 0.012, 0.018, respectively). A median weight reduction of 5% from baseline was observed. There was a reduction in median HbA1c to 7.7% (4.0), however, this was not statistically significant (P-value = 0.34). No change in TDD was observed (P-value = 0.85). Three patients (25%) experienced mild gastrointestinal symptoms, which did not require discontinuation of GLP1RA. CONCLUSION GLP1-RA is effective for weight loss even with a shorter treatment duration, while the effect on HbA1c and TDD reduction may require a longer treatment duration.